Department of Management, Faculty of Business Economics, Universitas Muhammadiyah Jember - Eko Budi Satoto (Jurnal Manajemen, 2024)
The supply chain of mining businesses listed on the Indonesia Stock Exchange (IDX) has declined due to the significant impact brought about by the uncertainty of an increasingly complex world economic climate. This study aims to determine the relationship between interest rates, inflation, currency exchange rates, stock returns, and firm value. Structural Equation Modeling (SEM) analysis was conducted to decipher the data in this study. The research findings show that the mining industry in Indonesia is highly influenced by macroeconomic factors, especially interest rates, inflation, and exchange rates. The negative relationship between interest rates and inflation negatively affects stock returns and firm value. Meanwhile, it increased the rupiah's value positively and significantly influenced stock returns and business value. Higher stock returns can increase the value of mining companies listed on the Indonesia Stock Exchange (IDX).